Is Electroencephalography Useful in Children with Developmental Delays but without Overt Seizures? - Yoo Jung Lee; Yoon Hee Jo; Soo Han Choi; Hye Won Yoo; Ha Young Jo; Su Jeong Park; Kyung Hee Park; Ju Hyun Kong; Yun Jin Lee; Sang Ook Nam; Young Mi Kim (Annals of Child Neurology, 2024)
Purpose Electroencephalography (EEG) is useful for clarifying the association between cortical activity and cognitive processes in children. We investigated whether EEG abnormalities were correlated with developmental delay/intellectual disability (DD/ID) in the absence of clinical seizures. Methods We retrospectively identified 166 children with DD/ID who underwent EEG at Pusan National University Hospital between January 2011 and December 2021. We compared clinical characteristics and test results between those with normal and those with abnormal EEGs. Additionally, we analyzed EEG abnormalities in relation to neurodevelopmental disorders, specifically autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). Results Of the 166 patients, 39 (23.5%) displayed abnormal EEGs, while 127 (76.5%) had normal EEGs. Of the former, 25 (64.1%) patients exhibited epileptiform discharges, including 22 (56.3%) with focal and three (7.7%) with generalized discharges. Focal discharges most frequently affected the central area (35.9%). Twenty patients (51.3%) exhibited rhythmic slowing patterns. Epilepsy diagnoses were significantly more common among patients with abnormal EEGs (n=8, 20.5%) than among those with normal EEGs (n=9, 7.1%) (P<0.001). Of 22 patients with ASD, five (12.8%) had abnormal EEGs. Of 13 patients with ADHD, five (36.4%) had abnormal EEGs, all with epileptiform discharges. Two patients with ASD and two with ADHD exhibited rhythmic slowing. Abnormal EEG findings were significantly more common among those with genetic abnormalities compared to genetically normal patients (26 vs. 13, P=0.017). Conclusion EEG represents a potential screening tool for children with DD. Abnormal EEG findings are associated with increased epilepsy risk, informing diagnosis and treatment planning.